Causation analysis of fire explosion in the port's hazardous chemicals storage area based on FTA‐AHP. Issue 1 (15th September 2022) - Chang, Yong; Zhang, Dehao
Abstract: At 22:51 on August 12, 2015, a fire explosion accident occurred in the hazardous cargo warehouse of the Ruihai Company, which is located in Tianjin Port, Binhai New Area, Tianjin. This accident killed 165 people and caused direct economic losses of 6.866 billion yuan. In order to reduce the occurrence and harm of fire explosion accidents in the port's hazardous chemicals storage area, the main influencing factors were analyzed using the fault tree analysis‐analytic hierarchy process (FTA‐AHP) method, and each factor was quantitatively analyzed. Taking a hazardous chemicals storage yard in Shanghai as an example, the cause of fire explosion in a hazardous chemicals storage area was obtained by establishing a fault tree analysis (FTA) and analytic hierarchy process (AHP). Then, the AHP model was established to calculate the weight of each influencing factor, and finally, the total weight ratio of each influencing factor was obtained. The results showed that human factors were the main and direct factors, equipment and facilities factors were the secondary factors, and management factors were the fundamental factors in fire explosion accidents in the port's hazardous chemicals storage areas. According to the evaluation results, a prevention and control strategy for fire explosion accidents in hazardous chemicals storage areas is proposed, which has reference value for relevant management departments.